Strategi Pengembangan Smart Village Menggunakan Enterprise Architecture TOGAF ADM 9.2 di Desa XYZ - Risma Sri Nur Hasanah; Luthfi Ramadani; Ryan Adhtya Nugraha (STMIK Budi Darma, 2023)
Improving the quality of life and ensuring equitable development are the primary focuses of the government in realizing a smart village (smart village). Facing increasingly complex development challenges, the integration between the Developing Village Index and the Sustainable Development Goals (SDGs) becomes vital to achieving sustainable development goals at the village level. This study investigates the implementation of Smart Village within the dimension of Smart Living, taking into account the Developing Village Index and the SDGs. The TOGAF ADM 9.2 framework is utilized as a guideline to design and implement information technology (IT) solutions based on sustainable development objectives and the needs of the village community. In this research, the stages of the TOGAF ADM 9.2 framework are employed to analyze the needs and sustainable development objectives in the village, identify the appropriate IT architecture and design applications and technology infrastructure to support the implementation of Smart Village. The result of this study is a holistic and integrated IT architecture design for a Smart Village within the Smart Living dimension, capable of bridging the development gap and achieving sustainable development at the village level. The implementation of Smart Village, focusing on the Developing Village Index and SDGs, has the potential to deliver positive impacts in enhancing the quality of life of the village community, increasing access to public services, and fostering village development.